A survey of the mutual effects of mobile phone usage on the citizenship culture in developing countries - Seyed Maziar Alavi; Seyed Hossein Hosseini; Ali Hosseini; Mohamad Samaei (Journal of Social Studies (JSS), 2022)
Information and Communication Technologies have made great changes to the lifestyle of human beings. Mobile phones, with their rapid growth in different parts of the world, essential parts of our lives. Mobile phone has helped to overcome location barriers and have had great impacts on the people’s lives, especially in urban areas. In developing countries, mobile phone has grown rapidly in the recent decade and has had great impacts on communications and other aspects of social life. The purpose of this study is to investigate the effects of the mobile phone technology push on the culture of citizens, in developing countries. Running a survey-type research, a sample of people in Tehran, the capital city of Iran, have been asked to fill a questionnaire; then, after gathering and cleansing and analysing the data, some recommendations are added that could be used in urban policy making in the various developing countries